Metodologia para a elaboração de mapa de potencialidade para a silvicultura com base em álgebra de mapas - A porção paulista da bacia do Rio Paraíba Do Sul, Brasil - Sátiro, Talita Peixoto de Oliveira [UNESP]; Simões, Silvio Jorge Coelho [UNESP]; Automare, Giordano Bruno; Bernardes, George de Paula [UNESP]; Soares, Paulo Valladares; Trannin, Isabel Cristina de Barros [UNESP]; Dias, Juliano Ferreira (My University, 2013)
This study developed a methodology in order to identify the most appropriate areas for eucalyptus plantations based in the interactions among physical landscape elements using GIS. The area of study is the Paraiba do Sul basin (southeast of Brazil), which has been chosen for being an area where a cycle of great expansion of the eucalyptus plantation has begun in the last decades. This basin comprises nearly 15.300 km2 and it characterized by a complex heterogeneous landscape. The analysis of the physical elements took into account thematic maps (geology, geomorphology and pedology) obtained from CEIVAP project in AUTOCAD format and later was converted and adjusted in ArcGIS® environment. To each landscape feature (rocks and structures, relief, and soil) it was applied a scale factor which corresponds the most suitable (5) or the less suitable (1) for the forest eucalyptus management. The final map (Silviculture Potentiality Map) indicated the areas, which might be considered the most favorable to the eucalyptus plantations. The most suitable areas are associated with well-drained, homogeneous and thick soils (oxisoils) and reliefs with low and intermediate steepness. The less favorable areas are associated with two types of very different physical substrates: a) areas of steeper relief with substratum of acid granites rocks and shallow soils (cambsols) and b), areas under conditions of poor drainage and high water table level associated with Paraiba do Sul River (gleysols). Results have showed that about 80% of the total area could be considered very good or good for eucalyptus plantation. Most part of these suitable areas represent vast region of migmatites rocks associated with Mountain with Steeper Hillslope relief and relatively shallow soils. The Silviculture Potentiality Map constitutes an important tool for eucalyptus plantation management particularly for the forestry activities in mountainous regions.
Methodology for the preparation of statement of capability for forestry based algebra of maps - A portion of São Paulo Paraíba River Basin, South Brazil
Keywords: Eucalyptus management; Geographical information system; Physical elements